Challenges and Innovation of Indonesia Overseas Election in Tokyo - Gusti Raganata (Jurnal Politik)
Overseas election by Indonesia was started since 1955. However, the regulation of overseas election in Indonesia have a problem in the absence of specific rules regarding the law and almost no distinguishment between overseas and domestic election. It turns out that the Implication of lack of specific regulation are constraining the overseas election committee (PPLN) to run smooth simultaneous election and influencing quality of election. While Indonesia election are mostly done through a traditional based on paper election and manual data collection, PPLN promoting innovations to overcome the challenges. PPLN Tokyo face these constraints by applicating innovation technology solutions. Hence, several innovations done can be a lesson learned to be replicated domestically and to create better election quality.